Declining Quality Affects Choice: The Peruvian Case - Castro, Juan F.; Yamada, Gustavo (International Higher Education, 2013)
Few adolescents in the developing world receive sufficient guidance to make crucial life decisions during the transition from secondary to postsecondary education and into the labor market. Consequently, a significant number of graduates regret the decisions they make. The excessive rigidity of most higher education systems prevents lateral shifts between programs or from technical to university education. In addition, in Peru limited information about the range of programs and their labor market outcomes, combined with an increasing number of low-quality providers, contribute to the problem.